GA based algorithm for optimum allocation of reactive power under deregulated environment - Nidul Sinha; Loi Lei Lai; Ghosh, P.K. (2008 Third International Conference on Electric Utility Deregulation and Restructuring and Power Technologies, 2008)
An algorithm using floating point genetic algorithm (FPGA) was developed to solve the problem of optimum allocation of reactive power in power systems under open market environment. The performance of the proposed model is validated on IEEE-14 bus system with modifications to incorporate the varying working conditions of power systems like, change of tap settings of transformers, variable reactive power compensations, etc. Results of the FPGA demonstrate that the algorithm is well competent in achieving the near optimal allocation of reactive power under practical constraints and price based conditions.